Women Architects and Their Works in the Autonomous Region of Madrid, 1978-2008 - María Elia Gutiérrez Mozo; Sofía Parker San José (Feminismo/s)
This paper explores the periphery of the very centre of the architectural system in Spain, considering the work of women architects in the Autonomous Region of Madrid (Comunidad Autónoma de Madrid), the province of its capital, in the period 1978-2008, i. e., between the democratic restoration and the global financial crisis. The approach is threefold. Firstly, a quantitative analysis, according to various parameters, of a sufficiently representative sample (more than a hundred cases) of this female-authored production, either solo or in collaboration with other women colleagues. Secondly, an analysis of the presence of women and their works in the architectural media in terms of the prestige they represent. Thirdly, an evaluation based on a qualitative approach of these works, the account of their differential features, and the identification of the very interests that women architects expressed through them. To this end, a methodology is implemented that includes the collection of bibliographic sources, a call to the architects to invite them to submit their projects and field work, by visiting and collecting data from most of the works. The results reveal that most of their professional practice that solo and is mainly based on residential works—the most recognised— followed by interventions in public spaces. Most of the works correspond to new construction and are concentrated, in time, in the 1990s and, in space, to the south and east of both the capital and the wider Madrid Region. The work of women architects has hardly been reported in professional journals, although it has been more widely disseminated in institutional publications, especially in the case of female civil servants. Qualitatively, the attention paid to the programme, especially to the common and intermediate spaces, the suitability of the technical means to the ends and the context, the care taken in the design of inclusive public spaces and the commitment to sustainability are striking. All this speaks volumes about the value of authors and architectures that, even in the center itself, are relegated to the periphery. It is a political and cultural system, which gender-based research challenges to propose hopeful alternatives for the discipline.